2015
DOI: 10.1192/pb.bp.114.046896
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning and palliative medicine in advanced dementia: a literature review

Abstract: Aims and method To assess the factors that affect the clinical use of advanced care planning and palliative care interventions in patients with dementia. A literature search of Medline, Embase and PsycINFO was performed to identify themes in advanced care planning and palliative care in dementia.Results In total, 64 articles were found, including 12 reviews, and three key areas emerged: barriers to advanced care planning, raising awareness and fostering communication between professionals and patients, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…27 Given that LBD is an irreversible neurodegenerative disease, advance care planning (ACP) forms a major part of care. 28 Our data for dysphagia, aspiration pneumonia, pressure sores, and mortality can offer useful information during ACP for Chinese LBD patients. Since those patients who have died had a higher presenting CDR score, lower Barthel Index, and greater usage of levodopa (which probably reflects more severe parkinsonism), ACP should be initiated earlier in LBD patients with these features.…”
Section: Discussionmentioning
confidence: 79%
“…27 Given that LBD is an irreversible neurodegenerative disease, advance care planning (ACP) forms a major part of care. 28 Our data for dysphagia, aspiration pneumonia, pressure sores, and mortality can offer useful information during ACP for Chinese LBD patients. Since those patients who have died had a higher presenting CDR score, lower Barthel Index, and greater usage of levodopa (which probably reflects more severe parkinsonism), ACP should be initiated earlier in LBD patients with these features.…”
Section: Discussionmentioning
confidence: 79%
“…Advanced Care Plans are targeted interventions aiming to promote early decision-making for patients nearing the end of their lives 1. There is increasing evidence that this planning can allow patients greater autonomy as they lose capacity and improve the grieving process for patients’ families after death 2.…”
Section: Introductionmentioning
confidence: 99%
“…We know little about the sizeable group of community-dwelling people with dementia and those whose dementia is in the early stages; that is, mild dementia. 9 These previous studies have shown that residents with advanced dementia are at risk of undergoing burdensome interventions at the end of life, potentially avoidable hospitalizations from nursing homes and of dying with great suffering. [10][11][12][13][14] Cross-country comparisons regarding dying with dementia are limited.…”
Section: Introductionmentioning
confidence: 99%